The Comparison Between Lubuk Gadang and Pasir Talang Dialect in South Solok - Aditiawarman, Mac; Wahyuningsih, Sri (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research entitled the Comparison Between Lubuk Gadang and Pasir Talang Dialects in South Solok.The main objective of this research is to compare the dialects of Lubuk Gadang and Pasir Talang, both of which originate from the South Solok region. The research focuses on lexical similarities, lexical differences, and word formation processes within the two dialects. A qualitative descriptive approach was employed, with data collected through direct interviews, observation, note-taking, and audio recordings. This research is grounded in lexical theory, dialectology, and morphological theory. These frameworks were used to analyze the vocabulary of both dialects in order to identify similarities and differences, as well as to understand the word formation processes involved. The results of the analysis revealed that there are 692 lexical items that share similarities between the two dialects, while 92 lexical items exhibit form differences. Additionally, 73 vocabulary items were identified as having different forms but the same meanings. In terms of word formation, several morphological processes were found in both dialects, including borrowing 13 items, compounding 21 items, clipping 3 items, acronym 1 item, and derivation 12 items. These findings highlight the linguistic diversity and complexity within regional dialects in South Solok.